(untitled) (Innovative professional education, 2022)
Public-private partnership as a contractual agreement combines many stakeholders with different plans and goals. The structure of public-private partnership includes state, private and public sectors. Each of them has its own functions and tasks, and the structure itself can be quite complex and contain contractual agreements between the parties, including the state. The model of relations of the parties of the project participating in the conclusion of the agreement on public-private partnership is presented.